Pemanfaatan Ekstrak Daun Kemangi sebagai ‘Hand Sanitizer‘ di Lembaga Pendidikan alFalah, Sei Mencirim, Deli Serdan - Nurhayani Nurhayani; Yulvi Annisa Ahla Siregar (Jurnal Abdi Mas Adzkia, 2021)
ABSTRACT. Hand sanitizer is a non rinsed sanitizer which is can used to clean ourhands without water. Through community service activities, it is hoped to improve society’s insight about the importance in using hand sanitizer which is considered more effective than using soap and water to prevent the spread of virus so it can help people to avoid deseases which is caused by microbes. However, using hand sanitizer which contains high alcohol is dangerous because it can cause viral inflammation.. Using natural hand sanitizer which is made of Basil leaves is betterhand sanitizer solution naturally. Utilization of natural antiseptic which made ofbasil leaves extract is socialized in Al Falah School at Sei Mencirim village in orderto give information and insigt to students, parents’ students, teachers and staf thereabout how important to do prevention and avoidance deseases especially in pandemic covid-19 by keeping their hands clean through natural hand sanitizer use. Keywords: Hand sanitizer, Basil Leaves, Natural antiseptic